2017
DOI: 10.1002/jum.14202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Liver, Kidney, and Spleen Elasticity in Healthy Newborns and Infants Using Shear Wave Elastography

Abstract: Shear wave elastography can be used to measure liver, kidney, and spleen elasticity in newborns and infants. The standard values for abdominal organs allow differentiation of healthy versus pathological tissue. We measured the normal values of SWE in healthy newborns and infants as reference data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(54 reference statements)
1
10
2
3
Order By: Relevance
“…In the present study, we could not make comparisons regarding the accuracy of predicting HR‐EGV between 2D‐SWE and TE. However, 2D‐SWE measurements of the spleen were also reportedly measurable in healthy infants and the present study was able to measure SS by 2D‐SWE in all children. Spleen stiffness was found to be more accurate than LS as a predictor of HR‐EGV.…”
Section: Discussionmentioning
confidence: 52%
“…In the present study, we could not make comparisons regarding the accuracy of predicting HR‐EGV between 2D‐SWE and TE. However, 2D‐SWE measurements of the spleen were also reportedly measurable in healthy infants and the present study was able to measure SS by 2D‐SWE in all children. Spleen stiffness was found to be more accurate than LS as a predictor of HR‐EGV.…”
Section: Discussionmentioning
confidence: 52%
“…The blank spaces represent a lack of information. References for brain (Gunawan et al, 2015;Kaster et al, 2011;Law et al, 1985;Liu et al, 2017;Morin et al, 2017;Pinton et al, 2011) for liver Civale et al, 2013;Degos et al, 2010;Freese & Lyons, 1977;Ito et al, 2017;Law et al, 1985;Liu et al, 2006;Palabiyik et al, 2017;Tzschatzsch et al, 2016;Wear et al, 1995) and for kidney (Gennisson et al, 2012;Grenier, Gennisson et al, 2013;Insana et al, 1992;Palabiyik et al, 2017) 2-6, 2-7, 2-8, and 2-9. .............................................................................................53 Table 2-7.…”
Section: List Of Figuresmentioning
confidence: 99%
“…In SWE, the newest of these methods, the liver stiffness is estimated by measuring the propagation velocity of shear wave in tissues, and the two‐dimensional ultrasound technique is used for real‐time comparison. It has the advantages of having good reproducibility, high spatial resolution and being a quantitative evaluation that is not affected by compression artifacts . TE has some limitations in young children; some authors reported technical failure in 17% of children younger than 2 years old, and others reported technical failure in 10% of children of any age .…”
Section: Introductionmentioning
confidence: 99%
“…It has the advantages of having good reproducibility, high spatial resolution and being a quantitative evaluation that is not affected by compression artifacts. 5 TE has some limitations in young children; some authors reported technical failure in 17% of children younger than 2 years old, and others reported technical failure in 10% of children of any age. 6 SWE is a noninvasive imaging technique that shows promising reliability and clinical utility for the quantitative assessment of liver tissue stiffness, particularly in children.…”
Section: Introductionmentioning
confidence: 99%